2014
DOI: 10.1161/circheartfailure.113.000529
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physical Activity and Sedentary Time on the Risk of Heart Failure

Abstract: Background— Although the benefits of physical activity for risk of coronary heart disease are well established, less is known about its effects on heart failure (HF). The risk of prolonged sedentary behavior on HF is unknown. Methods and Results— The study cohort included 82 695 men aged ≥45 years from the California Men’s Health Study without prevalent HF who were followed up for 10 years. Physical activity, sedentary time, and behaviora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(93 citation statements)
references
References 39 publications
4
84
0
5
Order By: Relevance
“…[15][16][17] In contrast, the role of PA in reducing risk of HF has not been emphasized in existing guidelines and public health recommendations. 15 Although observational cohort studies have reported an inverse association between higher levels of PA and HF risk, [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] a comprehensive assessment of the quantitative dose-response association between PA and HF risk has not been previously reported. Understanding this relationship is important because recent studies suggest that there may be important differences in the mechanisms through which PA modifies HF risk and CHD risk, 20 and the dose of PA needed to significantly lower HF risk may differ from that currently recommended to reduce CHD risk.…”
Section: Editorial See P 1777 Clinical Perspective On P 1794mentioning
confidence: 99%
“…[15][16][17] In contrast, the role of PA in reducing risk of HF has not been emphasized in existing guidelines and public health recommendations. 15 Although observational cohort studies have reported an inverse association between higher levels of PA and HF risk, [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] a comprehensive assessment of the quantitative dose-response association between PA and HF risk has not been previously reported. Understanding this relationship is important because recent studies suggest that there may be important differences in the mechanisms through which PA modifies HF risk and CHD risk, 20 and the dose of PA needed to significantly lower HF risk may differ from that currently recommended to reduce CHD risk.…”
Section: Editorial See P 1777 Clinical Perspective On P 1794mentioning
confidence: 99%
“…20,21 The US-based studies included multiethnic populations; but overall the proportion of white individuals in these studies was >50%. Two studies enrolled men only 19,23 and one only women, 21 whereas the rest enrolled both the sexes. The age range of participants was 25 to 97 years.…”
Section: Data Synthesis and Statistical Analysismentioning
confidence: 99%
“…8 It is well known that physical inactivity is related to health impairments, but sedentary behavior has recently emerged as a new independent risk factor for chronic diseases as well as for mortality, regardless of moderate-to-vigorous physical activity. [9][10][11][12][13][14] Examples of sedentary behavior include watching television, sitting, playing video games and using computers. 15 Current studies have been investigating associations of physical activity and sedentary behaviors separately or combined.…”
Section: Introductionmentioning
confidence: 99%